Atributos quantitativos de espécies arbóreas pioneiras e não pioneiras da Floresta Atlântica - Macieira, Bernardo Pretti Becacici (2015)
The succession classification is based on very inconsistent quality attributes. The present study aimed to quantifysome phenotypicaspects in pioneer and non-pioneer tree species of the Atlantic Forest in the state of Espírito Santo. Leaves and stem segments of three pioneer species (Senna multijuga var. verrucosa, Miconia cinnamomifoliaandBixa arborea) and three non-pioneer species (Melanoxylon brauna, Carpotroche brasiliensisandNeoraputia alba)were analyzed. The pioneer species showed higher chloroplastid pigments; higher stomatal density and vessels elements diameters; higher glucose (6% of the dry mass –DM), fructose (2.3% DM) and sucrose contents (7.9% DM) found on the stem. Non-pioneer species showed higher leaf thickness, higher starch (2.8% DM) and cell wall polymers contents in their leaves (10% cellulose, 15% hemicellulose and 4% lignin DM). In the stem, the wall cell polymers contents in non-pioneer species (33% cellulose, 24% hemicellulose and 22% lignin DM) were higher than the pioneer species. The hemicellulose for both functional groups suggest that xylan (stem) and arabinogalactan (leaves) type. Whereas the soluble carbohydrates, starch and pigments are unstable molecules subject to environmental variations, we conclude that cell wall polymersare safer to characterize the functional classes. However, the lignin compound that was more varied between two functional groups (>100%) indicating that the content of polymer is more reliable quantitative attribute to identify pioneer and non-pioneer species from Atlantic Forest